Vadba za zdrave starostnike - Bajda, Kaja (Šport (Ljubljana), 2017)
The purpose of research was to find out how the selected strength exercise programme influences the movement efficiency, alteration in strength of the upper and lower extremities and aerobic endurance. Since experts have recently laid a lot of stress on strength exercise as one of the most adequate physical activity for the elderly, we drew up a 12-week, 60-minute strength exercise programme, carried out twice a week by the elderly submitted to the programme. The sample of subjects consisted of 10 elderly participants over the age of 65 and of both genders. They were active in the DCA-centre (Dnevni center aktivnosti) Zalog pri Ljubljani. During the measurement period they were healthy and without injuries or pains. We applied the Senioris Test Battery, conducted of 5 tests. The results have shown that the strength exercise programme intensifies the strength of the upper and lower extremities and the aerobic endurance, whereas the efficiency of both selected movements remains unchanged. On the basis of this research we could conclude that positive effects of the strength exercise could be confirmed in the elderly as well.
Keywords: elderly; gibalna učinkovitost; movement capability; sport; starostniki; strength exercise; šport; vadba za moč